Oil-producing flowers within the Iridoideae (Iridaceae): evolutionary trends in the flowers of the New World genera - Chauveau, Olivier (Oxford University Press, 2012)
BACKGROUND AND AIMS: Oil-producing flowers related to oil-bee pollination are a major innovation in Neotropical and Mexican Iridaceae. In this study, phylogenetic relationships were investigated among a wide array of New World genera of the tribes Sisyrinchieae, Trimezieae and Tigridieae (Iridaceae: Iridoideae) and the evolution of floral glandular structures, which are predominantly trichomal elaiophores, was examined in relation to the diversification of New World Iridaceae. METHODS: Phylogenetic analyses based on seven molecular markers obtained from 97 species were conducted to produce the first extensive phylogeny of the New World tribes of subfamily Iridoideae. The resulting phylogenetic hypothesis was used to trace the evolutionary history of glandular structures present in the flowers of numerous species in each tribe. Hypotheses of differential diversification rates among lineages were also investigated using both topological and Binary-State Speciation and Extinction methods. KEY RESULTS AND CONCLUSIONS: Floral glandular structures and especially trichomal elaiophores evolved multiple times independently in the American tribes of Iridoideae. The distribution pattern of species displaying glandular trichomes across the phylogeny reveals lability in the pollination system and suggests that these structures may have played a significant role in the diversification of the Iridoideae on the American continent.